A dual sgRNA library design to probe genetic modifiers using genome-wide CRISPRi screens - Alina Guna; Katharine R. Page; Joseph M. Replogle; Theodore K. Esantsi; Maxine L. Wang; Jonathan S. Weissman; Rebecca M. Voorhees (BMC Genomics, 2023)
Abstract Mapping genetic interactions is essential for determining gene function and defining novel biological pathways. We report a simple to use CRISPR interference (CRISPRi) based platform, compatible with Fluorescence Activated Cell Sorting (FACS)-based reporter screens, to query epistatic relationships at scale. This is enabled by a flexible dual-sgRNA library design that allows for the simultaneous delivery and selection of a fixed sgRNA and a second randomized guide, comprised of a genome-wide library, with a single transduction. We use this approach to identify epistatic relationships for a defined biological pathway, showing both increased sensitivity and specificity than traditional growth screening approaches.